Spatial variation in soil properties and crop yield on stone bund terraces in southwest Ethiopia. (12th November 2021) - Wolka, Kebede; Biazin, Birhanu; Martinsen, Vegard; Mulder, Jan
Abstract: Erosion and associated soil degradation are major threats to cropland productivity on the steep slopes of the Ethiopian highlands. To limit erosion from cultivated land on sloping terrain, stone bunds for soil conservation have been used for decades, resulting in the formation of terraces. Although qualitatively well known, the difference in soil properties and crop performance between the upper and lower sections of the terraces (intra‐bund areas) has not been documented quantitatively. Here, we assess differences in soil properties of the plough layer and crop performance in the upper and lower sections of terraces in between stone bunds in southwest Ethiopia. A total of 27 terraces, with a length of 28.5–57 m and a distance of 6.5–14.7 m in between adjacent stone bunds, were sampled on six different farms during the 2018 and 2019 cropping seasons. The difference in soil properties was analysed using analysis of variance (ANOVA). Results showed that, in the lower section of a terrace, the concentration of soil organic carbon (18.6 g kg −1 ), total soil nitrogen (2.1 g kg −1 ) and exchangeable potassium (328 mg kg −1 ) was significantly greater ( p < .01) than in the upper section. Also, grain yield and biomass of maize, teff, broad bean and sorghum were significantly greater ( p < .05) in the lower section. This was particularly true for maize for which the yield in 2018 increased from 0.7 t ha −1 in the upper sections to 2.6 t ha −1 in the lower sections. Optimizing crop yields on terraces requires adaptive fertilizer application and crop choice.